LIVING WITH TRAUMA: AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS OF A HINDU’S RESILIENCE AFTER NATURAL DISASTERS IN SIGI BIROMARU - Otniel Aurelius Nole (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The natural disasters that struck the Sigi Biromaru area resulted in PTSD (posttraumatic stress disorder), as experienced by a Hindu survivor. Nevertheless, he organised resilience that focused on emotional and spiritual concerns. This research aimed to investigate a Hindu survivor’s resilience after natural disasters in Sigi Biromaru. Based on qualitative methods utilised the interpretative phenomenological analysis (IPA) approach, this research identified three main themes: traumatic experiences, emotional resilience, and spiritual resilience. The research evidenced that the participant has emotional and spiritual resilience as a foundation for overcoming trauma. Emotional resilience is when the survivor can deal with traumatic experiences by developing skills that support emotional balance, such as engaging in positive activities, pursuing hobbies and maintaining a healthy mindset. In addition, spiritual resilience, such as belief in God, praying and giving alms, is important in strengthening theological, psychological and sociological balance. Ultimately, this research contributes to an understanding of the strength of emotional and spiritual resilience that plays a role in shaping the spirit to survive and continue life of an individual who is still experiencing trauma, as well as its implications in the context of handling trauma after natural disasters.